Photograph of the site where Louis Riel was executed in Regina, Northwest Territories, Canada - Unattributed (Trinity College Dublin, the University of Dublin, 2020)
Photograph of the site where Louis Riel was executed outside the Royal Canadian Mounted Police headquarters in Regina, Northwest Territories. From Michael Davitt’s tour of Northwest Canada in 1891. Written on the back: ‘The window on the gable is that out of which Louis Riel stepped when executed. The boarding underneath encloses the spot on which the scaffold was erected [Regina, Saskatchewan]’.